THE COMPLEXITY OF NEW MEDIA ON THE FARMING OF ETAWA GOATS IN PURWOREJO, CENTRAL JAVA, INDONESIA - DWININGTYAS PADMANINGRUM; TATAG HANDAKA; SUBEJO (CV KULTURA DIGITAL MEDIA, 2020)
Purworejo farmers have been farming Etawa goats for long years, ever since the Dutch colonialisation in the beginning of 1900s until now. As Information and Communication Technologies (ICTs) progresses (new media), these farmers have taken initiatives to use of ICTs for marketing and promoting their Etawa goats. The purpose of this study is first, to discover the complexity of new media in farming Etawa goats in Purworejo, Central Java and secondly, it aims to explain the process of production and reproduction of the government’s communication system in dealing with the complexity of new media. The research method uses explorative case study method. The research site of this study is Purworejo Regency with study sample comprising 11 out of the 16 districts, with purposive sampling as the sampling method. The demands and challenges become the complexity of the environment for the government’s communication system. The system should reduce their complexity in order to obtain information of the environment which will become the input for itself. This information is the one that will be used for the process of producing and reproducing. However, the government’s communication system has been slow in reducing the complexity of new media. The system doesn’t become adaptive with this complexity of the environment